The Madisonian turn : political parties and parliamentary democracy in Nordic Europe - Bergman, Torbjörn; Strom, Kaare (New comparative politics., 2011)
"The Madisonian Turn is an outstanding assessment of the functioning of democratic institutions in the Nordic countries. If democracy is in trouble in Scandinavia, then it is surely facing problems everywhere, so the book will be read carefully by those concerned about contemporary governance in all modern democracies."--Michael Gallagher, Trinity College, Dublin "This welcome and timely re-evaluation of Nordic politics constitutes a major contribution to comparative government, and is likely to stand as the definitive treatment of politics in the region for many years to come."--Peter Mair, European University Institute "This book is unique in its comparative scope and the wealth of information on the state of parliamentary democracy in the Nordic countries. It is particularly useful for the comparativists who do not come from these countries, because the original literature which it covers in detail is often not accessible for the English-speaking audience."--Hanspeter Kriesi, University of Zurich "The strength of The Madisonian Turn is to interface detailed empirical evidence on the dynamics of democratic politics in Scandinavia with an elaboration and test of rival theories of change in the politics of postindustrial democracies. This book is an inspiration for students of Northern Europe, but also for scholars of comparative legislatures and political parties more generally."--Herbert Kitschelt, Duke University Parliamentary democracy is the most common regime type in the contemporary political world, but the quality of governance depends on effective parliamentary oversight and strong political parties. Denmark, Finland, Iceland, Norway, and Sweden have traditionally been strongholds of parliamentary democracy. In recent years, however, critics have suggested that new challenges such as weakened popular attachment, the advent of cartel parties, the judicialization of politics, and European integration have threatened the institutions of parliamentary democracy in the Nordic region. This volume examines these claims and their implications. The authors find that the Nordic states have moved away from their previous resemblance to a Westminster model toward a form of parliamentary democracy with more separation-of-powers features--a Madisonian model. These features are evident both in vertical power relations (e.g., relations with the European Union) and horizontal ones (e.g., increasingly independent courts and central banks). Yet these developments are far from uniform and demonstrate that there may be different responses to the political challenges faced by contemporary Western democracies. Torbjörn Bergman is Professor of Political Science at Umeå University, Sweden. Kaare Strøm is Professor of Political Science at the University of California, San Diego. Jacket Credit: Heidi Hobde Dailey